2014
DOI: 10.1016/j.jegh.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of footwear and foot condition among rural Ethiopian school children

Abstract: Shoe wearing provided limited foot protection. Interventions are needed to build behavioral skills, including foot washing and wearing appropriate shoes that maximize foot protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 2 publications
(2 reference statements)
2
18
0
Order By: Relevance
“…We may therefore have underestimated the extent to which some children are barefoot outside of school and at risk of acquiring tungiasis. A previous study of schoolchildren in rural Ethiopia reported that 54% stated they consistently wore footwear in the three days prior to being interviewed[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We may therefore have underestimated the extent to which some children are barefoot outside of school and at risk of acquiring tungiasis. A previous study of schoolchildren in rural Ethiopia reported that 54% stated they consistently wore footwear in the three days prior to being interviewed[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that larvae may develop from eggs shed by gravid female fleas and complete their life-cycle within the shoe resulting in an increased risk of further infestation. Previous studies have shown that, despite wearing closed shoes, soil was still adherent to the feet and the inside of shoes of 50% of children in Ethiopia[ 23 ] and other authors have emphasised the need to keep shoes and socks free from eggs and larvae[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 4 Available evidence indicates that podoconiosis is preventable if individuals consistently use footwear and begin doing so early in life. 5–8 Footwear is also associated with low prevalence of other soil-transmitted diseases, 8 and has been shown to prevent the recurrence of attacks of adenolymphangitis among patients with lymphoedema 9 and to reduce foot complications in other diseases such as diabetes. 10 …”
Section: Introductionmentioning
confidence: 99%
“… 5 7 Inconsistent use of footwear is associated with increased risk of acquiring soil-transmitted and foot-related disease. 1 8 11–15 …”
Section: Introductionmentioning
confidence: 99%
“…Wearing shoes provides only partial protection. One large study found heel cracks and foot trauma present regardless of shoe type . Therefore, maintaining SBF health and effective washing of feet and legs are essential in podoconiosis prevention.…”
mentioning
confidence: 99%